Starting fresh: a mixed method study of follower job satisfaction, trust, and views of their leader’s behavior - Spector, Paul E.; Howard, David J.; Eisenberg, Eric M.; Couris, John D.; Quinn, Joann F. (Frontiers in Psychology, 2024)
The leadership literature has been dominated by the study of broad styles rather than the identification of specific key behaviors. To address this deficiency a mixed method approach was utilized to explore how follower behavioral descriptions of their leaders would relate to potential outcomes of trust in that leader and job satisfaction. Data were collected from 273 hospital direct reports of 44 managers. They were asked to first describe the leadership approach of their managers in their own words, and then complete quantitative measures of the two potential outcomes. The qualitative responses were coded into nine leadership behavior themes listed here in order from most to least often mentioned: Kindness, Supportive, Open to Input, Allow Autonomy, Engage with Team, Transparency, Fairness, Professionalism, Hold Accountable. All behavior themes related significantly to trust of the leader, with three themes relating significantly to job satisfaction (Transparency, Fairness, and Professionalism).